Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Plant Defensin PgD1 a Biotechnological Alternative Against Plant Pathogens - Alaide Cristina de Bem Matos; Elisa Maria Rodriguez Pazinatto Telli; Luana Coldebella Camillo; Gustavo Felippe da Silva; Mayra Juline Gonçalves; Ricardo Casa; Leo Rufato; Maria de Lourdes Borba Magalhães (Probiotics and Antimicrobial Proteins, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Structural insights into ABA receptor agonists reveal critical features to optimize and design a broad-spectrum ABA signaling activator - Mar Bono; Cristian Mayordomo; Alberto Coego; Jonatan Illescas-Miranda; Maria Rivera-Moreno; Lourdes Infantes; Pablo López-Carracedo; Mayra Sanchez-Olvera; Constanza Martin-Vasquez; Gaston A. Pizzio; Javier Merino; Javier Forment; et al. (Molecular Plant, 2025)

Cancer fatalism, social media informational awareness, and education - Jim P. Stimpson; Sungchul Park; Mayra Rodriguez; Miguel Ángel Cano; Alexander N. Ortega (Cancer Causes & Control, 2024)

Connecting blue-green infrastructure elements to reduce combined sewer overflows - Giovan Battista Cavadini; Mayra Rodriguez; Lauren M. Cook (Journal of Environmental Management, 2024)

Do baseline assumptions alter the efficacy of green stormwater infrastructure to reduce combined sewer overflows? - Mayra Rodriguez; Giovan Battista Cavadini; Lauren M. Cook (Water Research, 2024)

The effect of green infrastructure on resilience performance in combined sewer systems under climate change - Mayra Rodriguez; Guangtao Fu; David Butler; Zhiguo Yuan; Lauren Cook (Journal of Environmental Management, 2024)

Global resilience analysis of combined sewer systems under continuous hydrologic simulation - Mayra Rodriguez; Guangtao Fu; David Butler; Zhiguo Yuan; Lauren Cook (Journal of Environmental Management, 2023)

Barriers and opportunities for waste pickers within solid waste management policy in Colombia - Alejandra Gómez-Maldonado; Laura Catalina Ospina-Espitia; Paul Rodríguez-Lesmes; Mayra Alejandra Rodríguez-Rodriguez (Waste Management, 2023)

Assessment of Health Risk and Presence of Metals in Water and Fish Samples from Doce River, Brazil, After Fundão Dam Collapse - Amanda Oliveira Mourão; Mayra Soares Santos; Alexandre Sylvio Vieira da Costa; Heberson Teixeira da Silva; Luiz Fernando Oliveira Maia; Márcia Cristina da Silva Faria; Mariandry del Vale Rodriguez Rodriguez; Jairo Lisboa Rodrigues (Archives of Environmental Contamination and Toxicology, 2023)

Ataxia Myoclonus Syndrome in Mild Acute COVID-19 Infection - Sergio Rodriguez-Quiroga; Mayra Aldecoa; Nicolas Morera; Carolina Gatti; Cesar Gil; Nélida Garretto; Alfonso Fasano (The Cerebellum, 2022)

Protein compounds of Bacillus subtilis with in vitro antifungal activity against Pseudocercospora fijiensis (Morelet) - Mileidy Cruz-Martín; Eilyn Mena; Mayra Acosta-Suárez; Tatiana Pichardo; Eloisa Rodriguez; Yelenys Alvarado-Capó (Brazilian Journal of Microbiology, 2020)

Transmission Strategies Used by Gyrodactylus gasterostei (Monogenea) on Its Host, the Three-Spined Stickleback Gasterosteus aculeatus - Mayra I. Grano-Maldonado; Juan Moreno-Navas; Maria Amparo Rodriguez-Santiago (Fishes, 2018)
The monogenean Gyrodactylus gasterostei and its host, the three-spined stickleback Gasterosteus aculeatus, were employed as a model system to investigate the influence of gyrodactylid maturity on host transfer. Laboratory experiments included the determination of maturity (presence of a male copulatory organ) and reproductive status (presence of a daughter parasite) of the transmitting worms. Parasites with a male copulatory organ were more likely to abandon the host and attempt a host transfer. Additionally, in vivo video observation suggested that detached worms employ water turbulence to assist their effective transfer onto a new host.

Influence of dissolved organic matter and oil on the biosorption of BTEX by macroalgae in single and multi-solute systems - Mayra Cecilia Rodriguez-Hernandez; Carlos E. Flores-Chaparro; Jose Rene Rangel-Mendez (Environmental Science and Pollution Research, 2017)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Cellular target of helminthosporium sacchari Toxin in sugarcane tissue - Miguel Ramos-Leal; Alberto Ruiz; Rodolfo H. Maribona; Mayra Rodriguez; Eduardo Canales; Odelsa Ancheta; Orlando Coto (Sugar Tech, 2005)